Various Mappings of Verb 'Seeing' in Lio Language - Bataona, Yosef Demon (Lingual Journal of Language and Culture; Vol 2 No 2 (2016)DO - 10.24843/LJLC.2016.v02.i02.p06, 2016)
Natural Semantic Metalanguage (NSM) is based on the theory of semantic. Natural Semantic Metalanguage (NSM) use semantic as a detailed analysis of lexem. Detail analysis lexem is done to avoid the ambiguity of interpretation. Analysis on Natural Semantic Metalanguage (NSM) is used to identify the natural meaning of a Bahasa Lamaholot Dialek Lamaleras verb. Natural Semantic Metalanguage (NSM) is used because (1) Contact interlanguages, (2) mobilisation of the native speaker and (3) The competence of the bilingualism of the native speaker. This is an activity to documentate the fitures of the natural meaning of Lamaholot language of Lamaleras Dialect verb, especially verb that state ‘catch the fish’, such as ‘leo, pasa, tufa, bitu, v?to, tivang, v?da, nuang, puk?t, tuba, dop?, blik?, sajo, h?p?k, tiv? kep, baong.
Keywords: Natural Semantic Metalanguage, Lamaholot language, Lamaleras Dialect